2004
DOI: 10.1074/jbc.m400197200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycosylation in the Organic Anion Transporter OAT1

Abstract: Organic anion transporters (OAT) play essential roles in the body disposition of clinically important anionic drugs, including antiviral drugs, antitumor drugs, antibiotics, antihypertensives, and anti-inflammatories. We reported previously (Kuze, K., Graves, P., Leahy, A., Wilson, P., Stuhlmann, H., and You, G. (1999) J. Biol. Chem. 274, 1519 -1524) that tunicamycin, an inhibitor of asparagine-linked glycosylation, significantly inhibited organic anion transport in COS-7 cells expressing a mouse organic anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 6 publications
8
109
1
1
Order By: Relevance
“…These deviations likely result from slight differences in alignment of the long extracellular loop and differences in the energy minimization procedures. The rbOCT2 model also takes into account that residue Asn 39 is a glycosylation site in loop 1-2 and not present in domain 1 as based on the GlpT template (35,37). In the hOAT1 model, the Asn 39 was left in domain 1 as it did not affect the remaining alignment.…”
Section: Discussionmentioning
confidence: 99%
“…These deviations likely result from slight differences in alignment of the long extracellular loop and differences in the energy minimization procedures. The rbOCT2 model also takes into account that residue Asn 39 is a glycosylation site in loop 1-2 and not present in domain 1 as based on the GlpT template (35,37). In the hOAT1 model, the Asn 39 was left in domain 1 as it did not affect the remaining alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigation from our laboratory on the structure-function relationship of OATs revealed that glycosylation is necessary for the targeting of these transporters to the plasma membrane (17,18).…”
mentioning
confidence: 99%
“…After exiting the ER, hENT1 was translocated to the Golgi and glycosylated. Glycosylation probably plays a significant role in trafficking and function for a number of transporters including ENTs (Cai et al, 2005, Hendriks et al, 2004, Tanaka et al, 2004. hENT1 was then trafficked to the plasma membrane in association with the microtubule network in a variety of vesicles; in the plasma membrane hENT1 was co-localized with actin, which suggested that this transporter was anchored in the membrane by the actin cytoskeleton (Nivillac et al, 2011).…”
Section: Molecular Properties Expression and Mechanism Of Transport mentioning
confidence: 99%